2005
DOI: 10.1007/s10495-005-1877-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel sulfasalazine analogues with enhanced NF-kB inhibitory and apoptosis promoting activity

Abstract: The NF-kB transcription factor plays a key role in the regulation of apoptosis by modulating expression of a wide range of cell death control molecules. NF-kB also plays an important role in human diseases by promoting inappropriate cell survival. Small molecule inhibitors of NF-kB are therefore likely to provide novel therapeutic opportunities. Sulfasalazine (SFZ) is a synthetic anti-inflammatory comprising an aminosalicylate, 5-amino salicylic acid (5-ASA), linked to an antibiotic, sulfapyridine (SPY). SFZ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…Interestingly, sulfasalazine inhibits the kinase (inhibitor kappa kinase, IκK) that activates IκB, and thus may accelerate recovery from experimental fibrosis by clearance of activated stellate cells through apoptosis. 94,96 Because these activated cells typically express high levels of TIMP-1, a metalloproteinase inhibitor, their clearance leads to increased net activity of matrix degrading proteases.…”
Section: Pathways Of Stellate Cell Activation: a Moving Target Initiamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, sulfasalazine inhibits the kinase (inhibitor kappa kinase, IκK) that activates IκB, and thus may accelerate recovery from experimental fibrosis by clearance of activated stellate cells through apoptosis. 94,96 Because these activated cells typically express high levels of TIMP-1, a metalloproteinase inhibitor, their clearance leads to increased net activity of matrix degrading proteases.…”
Section: Pathways Of Stellate Cell Activation: a Moving Target Initiamentioning
confidence: 99%
“…Interestingly, sulfasalazine inhibits the kinase (inhibitor kappa kinase, IκK) that activates IκB, and thus may accelerate recovery from experimental fibrosis by clearance of activated stellate cells through apoptosis. 94,96 Because these activated cells typically express high levels of TIMP-1, a metalloproteinase inhibitor, their clearance leads to increased net activity of matrix degrading proteases.Finally, messenger RNA (mRNA) stabilization also contributes to increased gene expression during stellate cell activation. Specifically, there is a 16-fold increase in collagen alpha 1(I) mRNA stabilization during stellate cell activation as a result of interaction of a specific protein, αCP, to a specific sequence in the 3′ untranslated region of the mRNA, 97 and also involving the interaction of a 120-kilodalton protein with the 5′ stem-loop structure.…”
mentioning
confidence: 99%
“…10 Although it has been reported that NF-B inhibition does not result in HSC apoptosis, 7 several studies have indicated that NF-B inhibition is a potent mechanism to induce HSC apoptosis. 8,11 Thus, mechanisms to inhibit NF-B in HSC have potential therapeutic relevance.…”
mentioning
confidence: 99%
“…Kanzler et al 79 recently compiled more than 40 compounds that act on Toll-like receptors that are in clinical trials for treatment of certain cancers, such as breast cancer and melanoma; allergies to ragweed, dust mites and asthma; and infectious diseases, such as HIV and Hepatitis C. NF-kB is known for its role in controlling apoptosis, so it comes as no surprise that the transcription factor is involved in the development of certain cancer types. Constitutive activation of NF-kB is linked to malignancies such as multiple myeloma, chronic lymphocytic leukemia and several lymphomas; 30 therefore, small molecules which can modulate NF-kB activity may be potent therapeutics for certain cancers. Habens et al 30 demonstrate the effectiveness of sulfasalazine (SFZ) a synthetic small molecule, as an inhibitor of IKK, which also results in the inhibition of NF-kB and subsequent apoptosis.…”
Section: Differentiationmentioning
confidence: 99%
“…Constitutive activation of NF-kB is linked to malignancies such as multiple myeloma, chronic lymphocytic leukemia and several lymphomas; 30 therefore, small molecules which can modulate NF-kB activity may be potent therapeutics for certain cancers. Habens et al 30 demonstrate the effectiveness of sulfasalazine (SFZ) a synthetic small molecule, as an inhibitor of IKK, which also results in the inhibition of NF-kB and subsequent apoptosis. Additionally, they showed that certain SFZ analogues produced compounds that are even more highly effective in inducing apoptosis in chronic lymphocytic leukemia cells in vitro.…”
Section: Differentiationmentioning
confidence: 99%